2020
DOI: 10.1016/j.parkreldis.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of safinamide as an add-on therapy to L-DOPA for patients with Parkinson's disease: A randomized, double-blind, placebo-controlled, phase II/III study

Abstract: Introduction: Safinamide is a reversible and selective monoamine oxidase-B (MAO-B) and sodium channel inhibitor with demonstrated efficacy in mid-to late-stage Parkinson's disease (PD) as an adjunct to L-DOPA. This study aimed to confirm the efficacy and safety of safinamide in PD patients with wearing-off. Methods: This 24-week, multicenter, randomized, double-blind, placebo-controlled, parallel-group study included Japanese PD patients with wearing-off on L-DOPA treatment. Patients were randomized to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 23 publications
4
61
2
1
Order By: Relevance
“…Based on the UPDRS analysis, our real clinical practice study confirms that safinamide may improve motor symptoms, motor complications, and daily life activities in PD patients, which is in agreement with previous reports [2][3][4][5]29,30]. Supporting these findings, a recent meta-analysis that evaluated both motor function and the activities of daily life in PD patients treated with safinamide suggested that the drug not only improves scores for UPDRS Parts II and III over placebo [31] but also improves motor function, motor fluctuations, and quality of life in PD [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the UPDRS analysis, our real clinical practice study confirms that safinamide may improve motor symptoms, motor complications, and daily life activities in PD patients, which is in agreement with previous reports [2][3][4][5]29,30]. Supporting these findings, a recent meta-analysis that evaluated both motor function and the activities of daily life in PD patients treated with safinamide suggested that the drug not only improves scores for UPDRS Parts II and III over placebo [31] but also improves motor function, motor fluctuations, and quality of life in PD [31].…”
Section: Discussionsupporting
confidence: 92%
“…Safinamide is a reversible and selective monoamine oxidase B inhibitor (MAOIB) and glutamate release modulator [1]. Several trials have demonstrated that in advanced Parkinson's disease (PD), safinamide significantly improves "ON" time without causing troublesome dyskinesia, reduces "OFF" time, and improves scores on the Unified Parkinson's Disease Rating Scale (UPDRS), improving quality of life [2][3][4][5][6]. Thus, it is approved for the treatment of mid-to-late fluctuating PD patients as an add-on therapy alongside stable doses of levodopa alone or in combination with others drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, six studies met the inclusion criteria for qualitative and quantitative synthesis (009, 015, 016, MOTION, SETTLE, and ME2125-3) (Fig. 1) [28][29][30][31][32]. The screening process retrieved one completed study with not yet published data, NCT00605683 (MOTION).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…2) and daily OFF-time (Fig. 3) were assessed in PDwMF patients treated with l-dopa [30][31][32]. Safinamide 100 mg significantly increased ON-time without troublesome dyskinesia (MD = 0.95 h; 95% CI from 0.41 to 1.49; p = 0.0006; I 2 = 70%) and decreased OFF-time (MD = − 1.06 hours; 95% CI from − 1.60 to − 0.51; p = 0.0001; I 2 = 76%).…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation